2017
DOI: 10.1186/s40880-017-0182-y
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of fluoropyrimidine-based adjuvant chemotherapy on biliary tract cancer after R0 resection

Abstract: BackgroundThe optimal treatment strategy for biliary tract cancer (BTC) after curative-intent resection remains controversial. The purpose of this study was to evaluate the efficacy of fluoropyrimidine-based adjuvant chemotherapy for BTC patients undergoing microscopically margin-negative (R0) resection.MethodsWe retrospectively analyzed the clinical data of BTC patients who underwent curative-intent R0 resection. Patients were eligible if they received either fluoropyrimidine-based adjuvant chemotherapy or ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Several retrospective studies have evaluated the effect of adjuvant chemotherapy in resected biliary tract cancer. These reports have many flaws, including heterogeneous disease, limited numbers of patients, long study period and a variety of regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies have evaluated the effect of adjuvant chemotherapy in resected biliary tract cancer. These reports have many flaws, including heterogeneous disease, limited numbers of patients, long study period and a variety of regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on adjuvant chemotherapy for BTC [ 10 , 11 , 15 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. The multicentre randomized phase III trial PRODIGE 12-ACCORD 18 conducted by a French group failed to show the efficacy of gemcitabine and oxaliplatin (GEMOX) in treating BTC patients in an adjuvant setting [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding BTC, some studies showed that adjuvant S-1 improved the prognosis [ 14 , 15 ]. Given that S-1 contains the 5-fluorouracil (5-FU) prodrug tegafur [ 13 ], previous studies using 5-FU as adjuvant chemotherapy for BTC [ 21 , 23 ] have also suggested the potential efficacy of S-1. Recently, a multicentre randomized phase III trial of adjuvant chemotherapy for BTC (BILCAP) reported the efficacy of capecitabine, one of the prodrugs of 5-FU, with an OS of 53 months in the adjuvant group versus 36 months in the observation group ( p = 0.028) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, for patients with stages II and III BTC, chemotherapy significantly improved 5-year OS rate (52.4% vs 35.6%, P = .002) and 3-year RFS rate (55.5% vs 39.1%, P = .021) compared with observation. [15]…”
Section: Discussionmentioning
confidence: 99%